Organic Agri-Practices and Pharmacognostic Evaluation of Off- Seasoned Cultivated Madhulika: A Wonder Herb: Pharmaceutical Sciences-Pharmacognosy for better Therapy - Singh, Lalit Raj; Singh, Karan (International Journal of Life Science and Pharma Research, 2021)
The faulty and mechanical lifestyle is causing various physical, mental and psychosomatic disorders today. It causes approximately 5.8 million death tolls every year in India. Diseases and disorders such as cardiovascular disorders (CVDs), osteoporosis, anaemia, diabetes, obesity and irritable bowel syndrome (IBS) are escalating very rapidly. This research paper explores and unveils the organic agri-practices of the Madhulika (Eleusine coracana (L.) Gaertn.) cultivated in off-season along with pharmacognostic evaluation. WHO-GACP and GHPP practices also followed along with organic cultivation practices. Madhulika; a wonder herb, belonging to the Poaceae family was organically cultivated in our herbal field laboratory (no. 4) by our indigenous seeds sown line to line in experimental blocks. The field experimental work was conducted from the first week of October, 2018 to the last week of January, 2019 in the Department of Medicinal Plants Sciences at Dev Sanskriti Vishwavidyalaya, Haridwar (U.K), India. The crop duration was increased during off season cultivation but the yield of the crop remained unaffected. The crop showed a high germination percentage (92%) in off season. The results of different physical evaluation parameters are given as total Ash (4.267 % w/w), Acid-insoluble Ash (0.433 % w/w), Water-soluble Ash (1.666 % w/w), Alcohol soluble extractive (12 .8 % w/w) and Water soluble extractive (4 % w/w). On the basis of the findings of the result, it is concluded that the crop was organically cultivated without change in quality and yield even in the off season. The processed products from these organic produce may prove as an elixir in curing lifestyle related health problems. Further, it was found that secondary metabolites are highly biosynthesized during organic agri-practices and resulting in least accumulation of adverse effect precipitating agents.